Dust - Manchevski, Milcho; Ackroyd, Barry; Fiennes, Joseph; Wenham, David; Lester, Adrian (Pathé, 2003)
"Dust" is three movies in one: a spaghetti Western, an urban drama and a historical epic ... When a desperate thug robs a lonely old lady, he somehow ends up on the wrong end of her gun, forced to hear the story of her ancestors. In flashback, we learn about two brothers (David Wenham and Joseph Fiennes) who traveled to Macedonia in search of money and trouble. [www.nydailynews.com]